Hans Joachim Schädlich und die niederländische Lyrik Übersetzungen im verlegerischen Feld der DDR - Zajas, Paweł (De Gruyter, 2021)
Abstract: The paper reveals the backstage of a modern Dutch poetry anthology Gedichte aus Belgien und den Niederlanden (1977), published by an East-German publisher Volk & Welt. An analysis of the surviving correspondence, publishing reviews, and peritexts (afterwords) has shown the mechanisms of transfer in lite- rary translation to the GDR. This historical-literary case study illustrates the ways in which the political and cultural function of anthologies enabled the introducti- on of formal/content innovations into the East German literary system.
Keywords: socjologia literatury; NRD; literatura niderlandzka